Analisis Kinerja Keuangan Pada PT. GLOBALINDO ALAM LESTARI - Purwati, Mulia Inda (Fakultas Hukum dan Ekonomi Bisnis, 2023)
This Study entitled “ Analysis Of Financial Performance On PT. GLOBALINDO ALAM LESTARI. The purpose of this study were : 1. To determine the development of the Current Ratio (CR), Quick Ratio (QR), Cash Ratio, Total Assets Turn Over ( TATO), Fixed Assets Turn Over (FATO), Debt Ratio (DAR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Return on Investment (ROI) dan Return On Equity (ROE). 2. To determine the financial performance of PT. GLOBALINDO ALAM LESTARI. To achieve this goal in doing the following steps : 1. See the development of the financial performance of the PT. GLOBALINDO ALAM LESTARI by using Liquidity Ratios, Activity Ratios, Solvabilitas Ratios and Profitability Ratios. 2. Conduct an analysis of financial performance of the PT. GLOBALINDO ALAM LESTARI 0f 10 indicators of financial ratios